Asuhan Keperawatan Pada An. A Dengan Gangguan Sistem Pencernaan: Demam Tifoid Di Ruang Anggrek RSUD Surakarta - Nahdi, Muhammad rifqi; , Siti Arifah, S.Kp., M.Kes (2015)
Background: typhoid fever is a syndrome systemic acute classically was caused by salmonella thypi included in genus salmonella.Goal: for knowing nursing care with gastrointestinal disorders: typhoid fever with assessment, intervention, implementation,evaluation.Aim of Research: Diagnosis is emerging in the case of hyperthermia, deficient fluid volume, imbalanced nutrition less than body requirements. After nursing actions during 3x24 hours in getting the results already body temperature within normal limits, fluid needs are met, appetite does not appear, anxiety.Conclution:Nursing actions will be undertaken in patients is to provide warm compresses that fever is down, instruct the patient to drink fluids so that needs are met, collaboration with nutritionist to meet the nutritional needs, show on interesting videos so anxious reduced.Keyword:typoid fever, hyperthermia, deficient fluid volume, imbalanced nutrition less than body, ancious